2019
DOI: 10.3389/fevo.2019.00172
|View full text |Cite
|
Sign up to set email alerts
|

Monarch Butterfly Distribution and Breeding Ecology in Idaho and Washington

Abstract: Studies of monarch butterflies (Danaus plexippus) and their milkweed (Asclepias spp.) host plants in North America have focused primarily on monarch populations ranging east of the Rocky Mountains. We report the first systematic assessment of monarch butterfly and milkweed populations in the western states of Idaho and Washington, states at the northern tier of western monarch breeding range. Results of our 2-year study (2016)(2017) offer new insights into monarch breeding habitat distribution, characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 39 publications
(54 reference statements)
1
24
0
Order By: Relevance
“…The highest land cover preference risk was found with Cultivated Crops for all four milkweed species. Waterbury et al (2019) similarly found cultivated croplands had low utilization for northwestern milkweeds. We found a few A. oenotheroides in Cultivated Crops, and A. latifolia occurred in cultivated crops in cotton elds of the Texas panhandle in the 1960's to 1970's before the increased use of glyphosate resistant cotton (S. Feagley, Soil and Crop Sciences Department, TAMU, retired, personal communication).…”
Section: Land Cover Preference Risk Assessmentsmentioning
confidence: 94%
See 3 more Smart Citations
“…The highest land cover preference risk was found with Cultivated Crops for all four milkweed species. Waterbury et al (2019) similarly found cultivated croplands had low utilization for northwestern milkweeds. We found a few A. oenotheroides in Cultivated Crops, and A. latifolia occurred in cultivated crops in cotton elds of the Texas panhandle in the 1960's to 1970's before the increased use of glyphosate resistant cotton (S. Feagley, Soil and Crop Sciences Department, TAMU, retired, personal communication).…”
Section: Land Cover Preference Risk Assessmentsmentioning
confidence: 94%
“…6). Waterbury et al (2019) found highest utilization of northwestern milkweeds for grassland/herbaceous cover. Asclepias latifolia favors grasslands, plains and prairies, trails, rocky canyon slopes, railways, and roadsides (Woodson 1954;Hart et al 2000;Nabhan et al 2015).…”
Section: Land Cover Preference Risk Assessmentsmentioning
confidence: 94%
See 2 more Smart Citations
“…Until recently, unlike the eastern population, relatively little was known about many aspects of the biology and ecology of western monarchs [ 6 ]. However, research during the past five years has provided information on habitats, host plants, breeding [ 7 , 8 , 9 , 10 ], and migration [ 11 , 12 , 13 , 14 ]. Research has also helped document the continuing decline of western monarch populations [ 4 , 5 , 15 ].…”
Section: Introductionmentioning
confidence: 99%